EFEKTIFITAS PENGGUNAANWHITE PETROLEUM JELLY UNTUK PERAWATANLUKATEKANSTAGE 1 DIRUANG DIRAWAT INAPSILOAMHOSPITALS LIPPO VILLAGE - Zahara, Yana; Dewi, Ratna; Saptarini, Endang (Indonesian Journal of Nursing Health Science, 2016)
AbstractThe high incidence of pressure sores occurring in hospitals, describing the low quality of nursing care provided in a hospital. Based on data from the wound and press events that occurred in the Siloam Hospital Lippo Village in the period January to August 2013 found as many as 78 events a total of 16 417 patients from admission (0. 48%). Financial problems to use a wound care products that are already available, also remains a constraint in wound care. Therefore, this research is expected to help the patient in terms of the economy as white petroleum jelly easily available and the price is quite affordable, with due regard to their effectiveness in accelerating wound healing stage press I. This study was conducted to prove the effectiveness of the use of White Petroleum Jelly in the treatment of injuries hit the first stage in the inpatient unit Siloam Hospital Lippo Village.Desain this experimental study using a pattern of one group pre and post test design, with a total sample of 15 patients were taken through purposive sampling. Collecting data using Identity Form Respondents and Pressure Ulcer Scale Healing recorded on the first day and the third after being given white petroleum jelly. The characteristic feature of most of the respondents have more than 50 years of age, hospitalized more than two days, the incidence of hospital-acquired pressure ulcers, and many are already using decubitus mattress. Data analysis using the Wilcoxon Signed Rank Test, Value p value <0.05, then Ho is rejected, it means that there are differences in pressure sores before and after white petrolleum jelly, so it can be concluded that interventions such as the use of white jelly petrolleum effect for treatment of injuries hit the stage I. White petroleum jelly can be used as an alternative option in the treatment of injuries hit the stage I, because it proved effective enough to help the healing of injuries hit the stage I.Â Keywords:Effectiveness, Luka press stage I, white petroleum jelly, Wound Care